Sex differences in the association between ideal cardiovascular health and biomarkers of cardiovascular disease among adults in the United States: a cross-sectional analysis from the multiethnic study of atherosclerosis - Olatokunbo Osibogun; Oluseye Ogunmoroti; Martin Tibuakuu; Eve-Marie Benson; Erin D Michos (BMJ Open)
Objectives This study investigated the sex differences in the associations between ideal cardiovascular health (CVH), measured by the American Heart Association’s Life’s Simple 7 metrics, and cardiovascular disease (CVD)-related biomarkers among an ethnically diverse cohort of women and men free of clinical CVD at baseline.Setting We analysed data from the Multi-Ethnic Study of Atherosclerosis conducted in six centres across the USA (Baltimore, Maryland; Chicago, Illinois; Forsyth County, North Carolina; Los Angeles, California; New York, New York; and St Paul, Minnesota).Participants This is a cross-sectional study of 5379 women and men, aged 45–84 years old. Mean age (SD) was 62 (10), 52% were women, 38% White, 11% Chinese American, 28% Black and 23% Hispanic.Primary measures The seven metrics (smoking, body mass index, physical activity, diet, total cholesterol, blood pressure and blood glucose) were each scored as 0 points (poor), 1 point (intermediate) or 2 points (ideal). The total CVH score ranged from 0 to 14. The CVD-related biomarkers studied were high-sensitivity C-reactive protein, D-dimer, fibrinogen, homocysteine, high-sensitivity cardiac troponin T, N-terminal pro B-type natriuretic peptide (NT-proBNP) and interleukin 6. We examined the association between the CVH score and each biomarker using multivariable linear regression, adjusting for age, race/ethnicity, education, income and health insurance status.Results Higher CVH scores were associated with lower concentrations of all biomarkers, except for NT-proBNP where we found a direct association. There were statistically significant interactions by sex for all biomarkers (p<0.001), but results were qualitatively similar between women and men.Conclusion A more favourable CVH score was associated with lower levels of multiple CVD-related biomarkers for women and men, except for NT-proBNP. These data suggest that promotion of ideal CVH would have similarly favourable impact on the reduction of biomarkers of CVD risk for both women and men.